S-nitroso-N-acetylcysteine attenuates liver fibrosis in experimental nonalcoholic steatohepatitis - Mazo DF; de Oliveira MG; Pereira IV; Cogliati B; Stefano JT; de Souza GF; Rabelo F; Lima FR; Ferreira Alves VA; Carrilho FJ; de Oliveira CP (Dove Medical Press, 2013)
Daniel FC Mazo,1 Marcelo G de Oliveira,2 Isabel VA Pereira,1 Bruno Cogliati,3 José T Stefano,1 Gabriela FP de Souza,2 Fabíola Rabelo,1 Fabiana R Lima,4 Venâncio A Ferreira Alves,4 Flair J Carrilho,1 Claudia PMS de Oliveira1 1University of São Paulo School of Medicine, Department of Gastroenterology, Clinical Division, Hepatology Branch (LIM-07), Sao Paulo, Brazil; 2Institute of Chemistry, University of Campinas, Campinas, Sao Paulo, Brazil; 3University of Sao Paulo School of Veterinary Medicine and Animal Science, Department of Pathology, Sao Paulo, Brazil; 4University of São Paulo School of Medicine, Department of Pathology (LIM14), São Paulo, Brazil Abstract: S-Nitroso-N-acetylcysteine (SNAC) is a water soluble primary S-nitrosothiol capable of transferring and releasing nitric oxide and inducing several biochemical activities, including modulation of hepatic stellate cell activation. In this study, we evaluated the antifibrotic activity of SNAC in an animal model of nonalcoholic steatohepatitis (NASH) induced in Sprague-Dawley rats fed with a choline-deficient, high trans fat diet and exposed to diethylnitrosamine for 8 weeks. The rats were divided into three groups: SNAC, which received oral SNAC solution daily; NASH, which received the vehicle; and control, which received standard diet and vehicle. Genes related to fibrosis (matrix metalloproteinases [MMP]-13, -9, and -2), transforming growth factor ß-1 [TGFß-1], collagen-1a, and tissue inhibitors of metalloproteinase [TIMP-1 and -2] and oxidative stress (heat-shock proteins [HSP]-60 and -90) were evaluated. SNAC led to a 34.4% reduction in the collagen occupied area associated with upregulation of MMP-13 and -9 and downregulation of HSP-60, TIMP-2, TGFß-1, and collagen-1α. These results indicate that oral SNAC administration may represent a potential antifibrotic treatment for NASH. Keywords: nitric oxide, S-nitroso-N-acetylcysteine, fibrogenesis, NASH, diethylnitrosamine